Reputation and Entry - Jeffrey Butler; Enrica Carbone; Pierluigi Conzo; Giancarlo Spagnolo (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2012)
This paper reports results from a laboratory experiment exploring the relationship between reputation and entry in procurement. There is widespread concern among regulators that favoring suppliers with good past performance, a standard practice in private procurement, may hinder entry by new (smaller or foreign) firms in public procurement markets. Our results suggest that while some reputational mechanisms indeed reduce the frequency of entry, so that the concern is warranted, appropriately designed reputation mechanisms actually stimulate entry. Since quality increases but not prices, our data also suggest that the introduction of reputation may generate large welfare gains for the buyer.
Keywords: H57; L14; L15; 330; Entry; Feedback mechanisms; Governance; Incomplete contracts; Limited enforcement; Incumbency; Multidimensional competition; Participation; Past performance; Procurement; Quality; Reputation; Vendor rating